Wisconsin Vice Committee: Tales of Prostitution and Commercialized Vice (Wisconsin: 1913-1915) - Schubert, Peter (My University, 2010)
The Wisconsin Vice Committee was established to inspect the moral situation of the state of Wisconsin. It is the methods they used to gather their information, the content of the hearings they held, the recommendations they made, and other related issues such as law enforcement and legal age that will be discussed in the following article.
Keywords: Wisconsin Vice Commission; Prostitution--Wisconsin--History